Matter, Motion, and Laws of Motion of Matter - Khatri, Tilak Bahadur (Pursuits: A Journal of English Studies, 2023)
This article explores fundamental properties inherent in matter. It is relevant to identifying the role of matter over human consciousness and the development of the universe. The article addresses the research problems concerning the primacy of matter or consciousness, mutability or the immutability of the matter, and law-abided or random motion of matter. The article deals with the research problems through the review-based analysis of the dialectical materialistic critique of the basic properties of matter. The article reveals that matter is primary over consciousness and there is nothing immutable in the universe. Motion is inherent in a matter and it is law-abided. There are two contradictory aspects inside a thing and the unity between them is relative and the struggle is absolute. A thing comes to its qualitative change through its quantitative change and the qualitative change leads the thing to new quantitative change for the new qualitative change. The thing moves to a new stage of development negating the old one and after several negations, there is the repetition of the first one. This repetition does not signify just the replacement of the old one, but it will be more advanced both in quantity and quality.